2016
DOI: 10.18632/oncotarget.8067
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic roles for fibroblast growth factor receptor family members in malignant peripheral nerve sheath tumor

Abstract: BackgroundMalignant peripheral nerve sheath tumors (MPNST) are rare, highly malignant, and poorly understood sarcomas. The often poor outcome of MPNST highlights the necessity of identifying prognostic predictors for this aggressive sarcoma. Here, we investigate the role of fibroblast growth factor receptor (FGFR) family members in human MPNSTs.ResultsaCGH and bioinformatics analysis identified frequent amplification of the FGFR1 gene. FISH analysis revealed that 26.9% MPNST samples had amplification of FGFR1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…FGFRs are deregulated by amplification, point mutation, or translocation and amplification is the most common deregulation form in multiple cancer types [ 16 - 18 ]. Amplification of FGFR1 has been reported in 13%-22% squamous cell lung cancer [ 13 , 19 , 20 ], 20% breast cancer [ 12 , 21 ], 10%-17% head and neck squamous cell carcinoma [ 22 , 23 ], and 26.9% malignant peripheral nerve sheath tumor [ 24 ]. FGFR1 amplification induced a strong FGFR1 dependency that could be exploited therapeutically, and in vivo studies have demonstrated inhibition of the FGFR1 pathway with FGFR inhibitors that led to significant tumor shrinkage [ 13 , 25 ], and translational clinical trials are undertaken [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…FGFRs are deregulated by amplification, point mutation, or translocation and amplification is the most common deregulation form in multiple cancer types [ 16 - 18 ]. Amplification of FGFR1 has been reported in 13%-22% squamous cell lung cancer [ 13 , 19 , 20 ], 20% breast cancer [ 12 , 21 ], 10%-17% head and neck squamous cell carcinoma [ 22 , 23 ], and 26.9% malignant peripheral nerve sheath tumor [ 24 ]. FGFR1 amplification induced a strong FGFR1 dependency that could be exploited therapeutically, and in vivo studies have demonstrated inhibition of the FGFR1 pathway with FGFR inhibitors that led to significant tumor shrinkage [ 13 , 25 ], and translational clinical trials are undertaken [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present case, dysphagia and stagger were initially suspected to be side effects of oxycodone treatment. The clinical presentation of brain metastasis is characterized by the acute onset of neurological symptoms (1,7). The clinical symptoms of medullary metastasis may be similar to a medullary infarction, which include dysphagia, dysarthria, dysphonia, vertigo, contralateral deficits in pain and temperature sensation, and vomiting (9).…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastasis from soft tissue sarcomas, including MPNST, is rare with a reported prevalence of 1-6% of all soft tissue sarcomas (1,4,5). In particular, brain metastasis arising from soft tissue sarcomas, in the absence of lung metastasis, is considered a relatively rare event (1,4,5). Furthermore, to the best of our knowledge, no cases of medullary metastasis without preceding lung metastasis have been reported in the literature to date.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Let us take for example malignant peripheral nerve sheath tumors (MPNSTs) that arise from major or minor peripheral nerve branches or sheaths of peripheral nerve fibers, and are derived from Schwann cells or pluripotent cells of neural crest origin [2]. Zhou et al [3] investigated the role of fibroblast growth factor receptor (FGFR) family members in human MPNSTs via an integrated genomic and molecular study, providing evidence that FGFRs play a role in MPNST prognosis.…”
Section: Dear Editormentioning
confidence: 99%